Long Atrial Fibrillation Duration and Early Recurrence Are Reliable Predictors of Late Recurrence After Radiofrequency Catheter Ablation - Li, Zhitong; Wang, Shihao; Hidru, Tesfaldet H.; Sun, Yuanjun; Gao, Lianjun; Yang, Xiaolei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2022)
Background Recurrence after atrial fibrillation (AF) ablation is still common. Objective This study aimed to evaluate the predictive abilities of AF duration and early recurrence (ER) to discriminate high-risk patients for recurrence. Methods We enrolled 1,763 consecutive patients with AF who were scheduled to receive the index radiofrequency catheter ablation (RFCA) from January 2016 to August 2021 in Dalian, China. Long AF duration (LAFD) was considered if the course of AF lasted for ≥ 12 months. ER was defined as any atrial tachycardia (AT) or AF event longer than 30 s occurring within a 3-month post-RFCA. Results Late recurrence occurred in 643 (36.5%) of the 1,763 patients at a median of 35 months after RFCA. Multivariate analysis identified LAFD (hazard ratio (HR): 1.80, 95% confidence interval (CI): 1.38–2.35, p < 0.001) and ER (HR: 2.34, 95% CI: 1.82–3.01, p < 0.001) as strong independent predictors of late recurrence in non-paroxysmal AF. Similarly, LAFD (HR: 1.48, 95% CI: 1.20–1.84, p < 0.001) and ER (HR: 3.40, 95% CI: 2.68–4.30, p < 0.001) were significantly associated with late recurrence in paroxysmal AF. Receiver operating curve analyses revealed that the CAAP-AF (CAD, Atrial diameter, Age, Persistent or longstanding AF, Antiarrhythmic drugs failed, Female) had the highest predict power [area under ROC curve (AUC) 0.586]. The addition of ER and LAFD to the CAAP-AF score significantly improved risk discrimination for late recurrence after AF ablation from 0.586 to 0.686. Conclusion Long AF duration and ER were independently associated with late recurrence. The prediction performance of the CAAP-AF model for recurrence was improved by the addition of LAFD and ER.